The Future of Local Government in Europe Lessons from Research and Practice in 31 Countries - Bouckaert, Geert (Modernisierung des, 2017)
Over recent decades, local governments in Europe have come increasingly under pressure facing a multitude of old and new challenges. Consequently, a wave of political and administrative reforms aimed at coping with these pressures has changed local governance in many nations. Local governments are not only responsible for efficient administration, high-quality services and a legally correct execution of laws, but also for ensuring legitimacy, democratic participation, accountability and trust - often under the conditions of austerity. This volume presents research findings of an international project on local public sector reforms in 31 countries and derives advice for policymakers to shape the future of local governments in Europe. The authors address basic reform areas and key features of local governance like autonomy, performance and participation.